2021
DOI: 10.37723/jumdc.v12i1.483
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Two Roots in Permanent Mandibular Canine of Pakistani Population: A Cone Beam Computerized Tomography (Cbct) Study

Abstract: BACKGROUND & OBJECTIVE: Missed root/canal is one of the main causes of endodontic failure. Permanent mandibular canine is considered to be a single rooted tooth. The complex pattern of root canal system poses difficulty in the root canal treatment and the prognosis becomes uncertain if the debridement and obturation of the root canals is not satisfactory therefore our objective of the study is to assess frequency of two roots in permanent mandibular canine of Pakistani population using CBCT scan. MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…This is in conformity with another study conducted in Pakistan which reported an incidence of 5.22%. 16 In our study, the incidence of accessory canal was found to be 10.4%. This is in agreement with a similar study conducted in India which reported 12.8% incidence of accessory canal in canine.…”
Section: Discussionsupporting
confidence: 45%
“…This is in conformity with another study conducted in Pakistan which reported an incidence of 5.22%. 16 In our study, the incidence of accessory canal was found to be 10.4%. This is in agreement with a similar study conducted in India which reported 12.8% incidence of accessory canal in canine.…”
Section: Discussionsupporting
confidence: 45%
“…Previous reports described 0.2% of mandibular canines were observed with bi-roots, but lateral incisors were all single root in Malaysian population [4]. 5.2% of permanent mandibular canines were also observed with two roots in Pakistani population via CBCT [20]. It is also reported that 1.5% of mandibular canines in Brazilian population, 0.3% of mandibular canines in Iran population are noticed with double roots via CBCT [6,21].…”
Section: Discussionmentioning
confidence: 95%